The Growth‐Inhibiting Effects of Beef Fatty Acids on MCF‐7 Cells Are Influenced Mostly by the Depot Location and Inconsistently by the Biohydrogenation Intermediate Content. Issue 7 (26th September 2018) - Vahmani, Payam; Rolland, David C.; Gzyl, Katherine E.; Baines, Danica D. S.; Dugan, Michael E. R.
Abstract: Biohydrogenation intermediates (BHI) including conjugated linoleic acid (CLA) isomers are formed during ruminal biohydrogenation of polyunsaturated fatty acids (PUFA) in ruminants. Although many studies have examined the anticarcinogenic effects of CLA, few studies have reported the anticarcinogenic properties of BHI in their natural form found in dairy and beef fats. The present study compared the growth‐inhibitory effects of fatty acids from beef perirenal fat (PRF) or subcutaneous fat (SCF) with low or high levels of BHI in MCF‐7 human breast cancer cells. Cells were exposed for 72 h to media containing increasing doses (50 to 400 μM) of different beef fat treatments. Fatty‐acid analysis showed that BHI were readily incorporated into cell phospholipids (PL) in a treatment‐dependent manner, but higher BHI in PL did not consistently inhibit growth. Culturing with low‐BHI PRF or high‐BHI PRF did not lead to growth inhibition, but low‐BHI SCF inhibited growth, and inhibition was further increased by high‐BHI SCF. Other classes of fatty acids may, therefore, be interacting with BHI resulting in differential effects on growth inhibition in human breast cancer cells.